Analysis of Road Damage Factors Based on Vehicle Load and Volume on K.H. Zaenal Arifin Road Segment Cikulak – Cibogo - Solahudin, Nur; Putra Susanto, Muhammad Daffa (Green Publisher Indonesia, 2025)
Road damage on K.H. Zaenal Arifin Cikulak–Cibogo, characterized by potholes, crocodile cracks, and flooding, disrupts traffic and safety and is exacerbated by heavy vehicle loads and poor maintenance. This study analyzes damage factors (vehicle load, traffic volume) and assesses pavement conditions to recommend repair methods. A quantitative approach with field surveys, visual documentation, and PCI analysis was employed, supported by traffic volume conversion to passenger car units (smp) and ESAL calculations. The PCI score of 42 (